PERAN PEKERJA SOSIAL MASYARAKAT DALAM PELAYANAN SOSIALDI KOTA CIREBON JAWA BARAT - Sabar Riyadi (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
This study aims to identify and analyse the role of Community Social Workers (PSM) in social services in Cirebon City, West Java. Using a qualitative approach and case study method, this study explores how PSM carry out initiatives in addressing social issues, developing social welfare activities, providing social services, and coordinating and assisting government programmes. Data was obtained through in-depth interviews with two active PSM and the Head of the local Social Service, as well as observation and documentation. The results of the study indicate that PSM play a strategic role as initiators of social programmes, facilitators of community empowerment, and partners of the government in the implementation of social welfare programmes. The main challenges faced include limited resources and policy synchronisation. However, the participatory and collaborative approach applied by PSM has proven effective in creating positive impacts on community welfare. This study recommends strengthening the capacity and structural support for PSM to improve the effectiveness of social services at the local level.